2021
DOI: 10.3390/risks9050081
|View full text |Cite
|
Sign up to set email alerts
|

Is Economic Uncertainty a Risk Factor in Bank Loan Pricing Decisions? International Evidence

Abstract: Uncertainty in economic environment leads economic agents to act cautiously. In this paper, we postulate that such uncertainty leads banks to charge higher interest rate on loans. Measuring aggregate country-level economic uncertainty with the World Uncertainty Index (WUI) and using a bank-level dataset from 88 countries over the period 1998–2017, we find that heightened economic uncertainty increases bank loan interest rates. Specifically, bank loan interest rates rise by 20.67 basis points with a one standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Additionally, Cui et al ( 2021 ) found that the effect of EPU on corporate innovation investment is negatively significant. Ashraf ( 2021 ) using data from World Uncertainty Index (WUI) on a bank-panel of 88 countries found that high uncertainty raises interest rates on bank loans, which in turn, reduces investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Cui et al ( 2021 ) found that the effect of EPU on corporate innovation investment is negatively significant. Ashraf ( 2021 ) using data from World Uncertainty Index (WUI) on a bank-panel of 88 countries found that high uncertainty raises interest rates on bank loans, which in turn, reduces investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are in a position that requires significant dependence on fluctuating natural conditions, placing them at higher economic risk than formal employment. The concept of uncertainty in economic theory (Ashraf, 2021), which explains how individuals make decisions in situations with incomplete or changing information, can provide insights into how river rock gatherers manage the risks associated with their work.…”
Section: Working Hoursmentioning
confidence: 99%
“…In addition to addressing the question of how to measure EPU, scholars have studied the impact of EPU on macro-and microeconomic fluctuations. In macro studies, uncertainty shocks are found to raise bank lending rates and lead to sharp fluctuations in the stock market [31,32]. Such shocks may also depress GDP growth, leading to a macroeconomic downturn [33], which, in turn, affects economic recovery [34].…”
Section: Literature Reviewmentioning
confidence: 99%